A survey on big data analytics for enhanced security on cloud - Anandan, R; Phani Kumar, S; Kalaivani, K; Swaminathan, P (International Journal of Engineering and Technology, 2018)
Cloud based data storage has become a common activity these days. Because cloud storage offers more advantages than normal storage methods those are dynamic access and unlimited storage capabilities for pay and use. But the security of the data outsourced to the cloud is still challenging. The data owner should be capable of performing integrity verification as well as to perform data dynamics of his data stored in the cloud server. Various approaches like cryptographic techniques, proxy based solutions, code based analysis, homomorphic approaches and challenge response algorithms have been proposed. This survey depicts the limitations of the existing approaches and the requirements for a novel and enhanced approach that ensures integrity of the data stored in cloud enabling better performance with reduced complexity.Â Â